Evaluating and Comparing the Usability of Mobile Banking Applications in Saudi Arabia - Sarah Alhejji; Abdulmohsen Albesher; Heider Wahsheh; Abdulaziz Albarrak (Information, 2022)
In many countries, the rapid growth of the Internet and mobile technologies has led to the expansion of Internet banking, especially mobile banking. Many banks seek to provide integrated banking services through mobile applications (apps) to increase customer satisfaction and loyalty. A quick look at the reviews of the mobile banking apps in Saudi Arabia reveals different usability issues among these apps. This research analyzed, evaluated, and compared the usability of all Saudi mobile banking apps available for the iOS and Android systems. Usability (as defined by ISO 9241) was measured using three criteria—effectiveness, efficiency, and satisfaction. This research also identified and discussed the most critical weaknesses of the Saudi banks’ apps in regard to providing satisfactory solutions to developers. The results showed that the most critical issues existed in the user interfaces and functionality of the apps, especially those that frequently received updates. Furthermore, the lack of customer support made the interaction between banks and customers weak, leading to customer dissatisfaction.